A hypomorphic mutation in the mouse Csn1s1 gene generated by CRISPR/Cas9 pronuclear microinjection - A. V. Smirnov; T. A. Shnaider; A. N. Korablev; A. M. Yunusova; I. A. Serova; N. R. Battulin (Вавиловский журнал генетики и селекции)
Caseins are major milk proteins that have an evolutionarily conserved role in nutrition. Sequence variations in the casein genes affect milk composition in livestock species. Regulatory elements of the casein genes could be used to direct the expression of desired transgenes into the milk of transgenic animals. Dozens of casein alleles have been identified for goats, cows, sheep, camels and horses, and these sequence variants are associated with altered gene expression and milk protein content. Most of the known mutations affecting casein genes’ expression are located in the promoter and 3’-untranslated regions. We performed pronuclear microinjections with Cas9 mRNA and sgRNA against the first coding exon of the mouse Csn1s1 gene to introduce random mutations in the α-casein (Csn1s1) signal peptide sequence at the beginning of the mouse gene. Sanger sequencing of the founder mice identified 40 mutations. As expected, mutations clustered around the sgRNA cut site (3 bp from PAM). Most of the mutations represented small deletions (1–10 bp), but we detected several larger deletions as well (100–300 bp). Functionally most mutations led to gene knockout due to a frameshift or a start codon loss. Some of the mutations represented in-frame indels in the first coding exon. Of these, we describe a novel hypomorphic Csn1s1 (Csn1s1c.4-5insTCC) allele. We measured Csn1s1 protein levels and confirmed that the mutation has a negative effect on milk composition, which shows a 50 % reduction in gene expression and a 40–80 % decrease in Csn1s1 protein amount, compared to the wild-type allele. We assumed that mutation affected transcript stability or splicing by an unknown mechanism. This mutation can potentially serve as a genetic marker for low Csn1s1 expression.